2010
DOI: 10.1186/1749-8090-5-44
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term outcomes for Endoscopic versus Open Vein Harvest: a case control study

Abstract: BackgroundSaphenous vein remains the most common conduit for coronary artery bypass grafting with increasing uptake of minimally invasive harvesting techniques. While Endoscopic Vein Harvest (EVH) has been demonstrated to improve early morbidity compared to Open Vein Harvest (OVH), recent literature suggests that this may be at the expense of graft patency at one year and survival at three years.MethodsWe undertook a retrospective single-centre, single-surgeon, case-control study of EVH (n = 89) and OVH (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Two single-centre studies and one multi-centre cohort study have found that EVH does not increase the rate of adverse clinical outcomes following CABG 13 15 16. The multi-centre analysis of the Northern New England data from 2001 to 2004 found EVH to be associated with a significant reduction in long-term mortality (adjusted HR 0.74, 95% CI 0.60 to 0.92) 16.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two single-centre studies and one multi-centre cohort study have found that EVH does not increase the rate of adverse clinical outcomes following CABG 13 15 16. The multi-centre analysis of the Northern New England data from 2001 to 2004 found EVH to be associated with a significant reduction in long-term mortality (adjusted HR 0.74, 95% CI 0.60 to 0.92) 16.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike this present study, Dacey et al found EVH to be associated with an increased adjusted risk of requiring a return to the operating theatre (2.4 vs 1.7; p = 0.03) 16. The single-centre analysis by Ouzounian et al found EVH to have no association with either in-hospital (OR 0.93, p=0.56) or midterm adverse outcomes (HR 0.93, p=0.22), and the patients from the UK single-centre study were included in this grouped analysis 13 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid adoption of EVH results from a dramatic reduction in invasiveness compared to the open, traditional vein harvesting (OVH) technique. Several studies have shown 2- and 3-fold improvements in the rate of wound-related complications and infections for EVH 2,3 . The significant reduction in incision length when grafts are procured using EVH yields less wound-related pain (WMD=1.95, P=0.06; 95% CI: –0.10–4.01) 4 , and increased patient satisfaction 5 compared to OVH.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery bypass grafting (CABG) is one of the most common cardiac surgical procedures performed worldwide [ 1 ]. Despite arterial conduits having a superior long-term graft patency rate, the long saphenous vein is still the first choice conduit as a second graft in multi-vessel bypass grafts [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%